The Effectiveness Of Snakes And Ladders Game As Clean And Healthy Living Behavior Learning Media In Pandemic Period For Elementary Students - Muhammad Fajriannor TM; Nadya Novianty (Lambung Mangkurat University, 2022)
Health promotion is very important in the midst of the COVID-19 pandemic. Clean and healthy living behavior is one of the ways to prevent the transmission of COVID-19. Health promotion cannot be separated from media use as delivering information to the target. One of the media that can be used to the children’s target is the snakes and ladders game. The snakes and ladders game are an exciting educational game for school-age children so that they are interested in learning while playing and make it easier for students to accept the information provided. This study aims to analyze the effectiveness of the snakes and ladders game as a learning media for clean and healthy living behavior during a pandemic in student elementary, based on knowledge, attitudes and practices of children with clean and healthy living behavior to preventing COVID-19. This research is quantitative research with a quasi-experimental research method with a non-equivalent control group design. This research was conducted at the Elementary School of Aranio 01, Banjar Regency, South Kalimantan Province with 23 students as the subject from grades IV, V and VI. Data analysis using paired t-test. The results showed that there was an average value difference in knowledge about COVID-19 from the treatment group before the intervention, 2 weeks and 1 month after being given the intervention (p value = 0.005 and 0.017), there was an average value difference in attitudes towards COVID-19 in the treatment group before being given the intervention, 2 weeks and 1 month after being given the intervention (p value = 0.013 and 0.027). The snakes and ladders game are effective as a learning media to change student’s knowledge and attitudes toward clean and healthy living behavior to prevent COVID-19.